TAKSONOMI BUDAYA INFORMASI DALAM KONTEKS PELAYANAN PUBLIK BERBASIS E-GOVERNMENT DI KOTA MAGELANG - Joko Tri Nugraha; Retno Dewi Pramodia Ahsani (Jurnal Komunikasi dan Kajian Media, 2018)
Although in 2014 the Magelang City Government has compiled a grand design for the development of city government telematics, but most of the stages of e-government application development are currently still focused on providing websites and information services only. In general, the objectives of this research are: (1) Analyzing the taxonomy of information culture of public organizations in the City Government of Magelang; (2) Identifying the driving and inhibiting factors of e-government-based public services in the City of Magelang and; (3) Preparing appropriate policy recommendations so that public services based on e-government in the City of Magelang can run more optimally. The approach used is descriptive quantitative with descriptive statistical analysis techniques. Research location in Magelang City Government. Data collection techniques through questionnaire surveys, documentation and observation. The level of information culture maturity in the City Government of Magelang is influenced by several types of culture, including technocratic utopianism, anarchy, feudalism, dictactorship and federalism. The most dominant information culture is dictactorship culture.Keywords: information culture, e-government, public service